The foggaras of Bouda (Algeria): from drought to flood - Youcef Boutadara; Boualem Remini; Saida Benmamar (Applied Water Science, 2018)
Abstract Based on investigations and flow gauges that we conducted in all the foggaras of the Bouda Oasis during the period: 2015–2018, this article examines an original hydraulic phenomenon that occurred recently in the oasis of Bouda in the wilaya of Adrar (Algeria). The exploitation of the boreholes made during the 1980s in the export field of foggaras caused a drying of foggaras water. However, in 2015, the remoteness of the well field and the supply of drinking water by the water resources services led to an increase in foggara flows. At first, it was good news for farmers, but over time the phenomenon became worrying for the population, since the flow has not yet stabilized. The phenomenon is starting to grow; sebkhas and palm groves are today flooded by the surplus of waters of foggaras.